Does Ignorance of Economic Returns and Costs Explain the Educational Aspiration Gap? Representative Evidence from Adults and Adolescents - Philipp Lergetporer; Katharina Werner; Ludger Woessmann (Economica, 2021)
The gap in university enrolment by parental education is large and persistent in many countries. In our representative survey of German adults, 74% of university graduates, but only 36% of those without a university degree, favour university education for their children. The latter are more likely to underestimate returns and overestimate costs of university. Similarly, 75% of adolescents with university-educated parents, but only 51% without university-educated parents aspire to a university degree. Experimental provision of general return and cost information does not close the aspiration gap as treatment effects are at least as strong for individuals with a university background as for those without. Differences in economic preference parameters also cannot account for the educational aspiration gap.
Keywords: 330